Performance of Male Condoms When Used With and Without a Silicone Placebo Vaginal Ring—A Randomized, Crossover Trial. (1st September 2020) - Nel, Annalene; Malherbe, Mariëtte; van Niekerk, Neliëtte; Beksinska, Mags; Greener, Ross; Smit, Jennifer; Frezieres, Ron; Walsh, Terri
Abstract : Background: The dapivirine vaginal ring reduced the risk of HIV infection by approximately 30% in Phase III trials. To ensure higher levels of protection against HIV and sexually transmitted infections, women should be counseled to use condoms when using the vaginal ring. This article evaluates the compatibility of male condoms with a placebo vaginal ring. Methods: This was a 2-period crossover, randomized, noninferiority trial. Couples in 2 sites in the United States were randomized to male condom use, with and without a placebo silicone vaginal ring, and asked to use 4 male condoms in each period. The primary noninferiority end points were total clinical failure and their component failure events (clinical breakage or slippage). Frequencies and percentages were calculated for each failure mode and differences in performance of the 2 periods using the male condom without the ring as reference. Noninferiority was defined using a 3% margin at the 5% significance level. Safety and acceptability were also assessed. Results: Seventy couples were enrolled, and 68 completed the trial with a total of 275 male condoms used in each period. Total condom clinical failure rates were 2.2% and 4.0% in the presence and absence of the vaginal ring, respectively, with a difference of −1.9% (95% confidence interval: −5.3% to 1.5%), thereby demonstrating noninferiority when used with the ring. There was no difference in safety between the 2 periods. Discussion: Concurrent use of the placebo silicone vaginal ring had no significant effect on male condom functionality or safety outcomes.